Four boron atoms, four positive charges, and four skeletal electrons: a fluorescent [sigma]-aromatic tetraborane(4) - Widera, Anna; Wadepohl, Hubert; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2019)
Reaction of a ditriflatodiborane compound with the Lewis acids AlCl3 or GaCl3 leads to abstraction of the two triflate substituents and dimerization of the resulting dicationic diborane to give a σ-aromatic tetracationic tetraborane with a planar, rhomboid B4 core. The compound exhibits four skeletal σ-electrons involved in two (3c,2e) bonds and represents the first stable fourfold base-stabilized [B4H4]4+ analogue. The product is isolated from the reaction mixture in the form of bright orange crystals that display fluorescence. Further analysis shows that the new tetraborane(4) is stabilized in the solid state by the lattice energy. It exhibits an extremely high electron affinity and is only stable in solution after one-electron reduction to the radical cation.
Im Titel ist "Sigma" als griechischer Buchstaben dargestellt
Gesehen am 23.10.2019